Survei Minat Dan Motivasi Guru Ilmu-Ilmu Sosial Studi Lanjut Pada Program Studi Magister Pendidikan Sosiologi FKIP Untan Pontianak (Integralistik, 2022)
This study aims to determine the effect of interest and motivation of social science teachers in junior and senior secondary education units in the city of Pontianak on the choice of further studies to postgraduate study program of sociology master's education FKIP Untan. The research method used was a survey method through a questionnaire assisted by google form which was sent to 254 people as the research sample. The data collection technique is done by indirect communication. The data collection tool used was a questionnaire. The results of the research prove descriptively that the social science teachers in the junior and senior secondary education unit in Pontianak, it turns out that the average percentage for interest is very low where only (25%) and for motivation (47.24%). ) in choosing further studies to postgraduate masters of sociology education FKIP Untan. Interest and motivation factors when analyzed using a two-way ANOVA obtained quantitatively the influence of interest and motivation on the selection of further studies to postgraduate sociology education master's degree was only 38,% and the rest was influenced by other factors, 62%.